Investigating the chronological reduction potential of a urease inhibitor in respiration chambers. (April 2021) - Bobrowski, Anna B.; Derno, Michael; Kuhla, Björn; Hagenkamp-Korth, Frauke; Hasler, Mario; Hartung, Eberhard
Abstract : Ammonia emissions have wide-ranging negative consequences for human, animal and environmental health. Regulations including EU Directive 2016/2284 require European Union member states to reduce emissions. Dairy farming has one of the highest levels of ammonia emissions. Most dairy barns in Germany are naturally ventilated to meet higher animal welfare standards. However, these housing systems allow an uncontrolled direct release of emissions into the atmosphere. A novel mitigation method could be the use of a urease inhibitor. Although previous studies have noted the reduction potential of the inhibitor type K, the chronological course of the reduction is still unknown. This study investigates the inhibitory reaction by dividing the experiment into time slots to examine the chronological reduction in emissions. The inhibitor was found to reduce ammonia emissions by up to 37% at the 12-h time slot. This supports the assumption that the reduction potential of the inhibitor evolves over time. Highlights: First direct ammonia measurement of a urease inhibitor inside respiration chambers. First calculation of a reduction potential by testing a urease inhibitor. Urease inhibitor reduction potential ranged between 3% and 37%. First information of the chronological development could be provided. Indications of the inhibitor application process could be achieved.